Preface - Błachowski, Bartłomiej; Tauzowski, Piotr (Computer Assisted Methods in Engineering and Science, 2022)
The contents of this special issue comprise four research papers devoted to engineering optimization, three of which were presented during the 2nd edition of the Workshop on Engineering Optimization (WEO-2021). The workshop was held in Warsaw, Poland, on October 7–8, 2021. Due to the COVID-19 pandemic, the 2021 edition of the workshop was organized in a hybrid form and was dedicated to the exchange of experiences in the field of engineering optimization including its theoretical and algorithmic aspects as well as practical applications. The workshop hosted six invited lectures and six thematic sessions. 21 presentations by authors from seven European and non-European countries (50% of them from outside Poland) were delivered.Additionally, the organization of the second edition of WEO was supported by the project entitled Development of regional network on autonomous systems for structural health monitoring financed by the Visegrad Fund, under the grant agreement 22110360. More details on the workshop and the V4SHM project can be found on the following website: http://v4shm.ippt.pan.pl.